A New Mixed Nonpolynomial Spline Method for the Numerical Solutions of Time Fractional Bioheat Equation - Abdullhussein, Ammar Muslim; Al-Humedi, Hameeda Oda (Iraqi Journal of Science, 2020)
In this paper, a numerical approximation for a time fractional one-dimensional bioheat equation (transfer paradigm) of temperature distribution in tissues is introduced. It deals with the Caputo fractional derivative with order for time fractional derivative and new mixed nonpolynomial spline for second order of space derivative. We also analyzed the convergence and stability by employing Von Neumann method for the present scheme.